2016
DOI: 10.1021/acschemneuro.6b00354
|View full text |Cite
|
Sign up to set email alerts
|

MK-801 (Dizocilpine) Regulates Multiple Steps of Adult Hippocampal Neurogenesis and Alters Psychological Symptoms via Wnt/β-Catenin Signaling in Parkinsonian Rats

Abstract: Adult hippocampal neurogenesis is directly involved in regulation of stress, anxiety, and depression that are commonly observed nonmotor symptoms in Parkinson's disease (PD). These symptoms do not respond to pharmacological dopamine replacement therapy. Excitotoxic damage to neuronal cells by N-methyl-d-aspartate (NMDA) receptor activation is also a major contributing factor in PD development, but whether it regulates hippocampal neurogenesis and nonmotor symptoms in PD is yet unexplored. Herein, for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…After intraperitoneal dizocilpine (0.2 mg/kg), rats spent more time in the light chamber ( p < 0.01), and more contact time during the social interaction test ( p < 0.05) in comparison to 6-OHDA lesioned rats. This suggests that MK-801 ameliorates depressive-like behavior in 6-OHDA lesioned rats 54 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…After intraperitoneal dizocilpine (0.2 mg/kg), rats spent more time in the light chamber ( p < 0.01), and more contact time during the social interaction test ( p < 0.05) in comparison to 6-OHDA lesioned rats. This suggests that MK-801 ameliorates depressive-like behavior in 6-OHDA lesioned rats 54 .…”
Section: Resultsmentioning
confidence: 83%
“…There are reports of neuroprotection after acute dextromethorphan in a number of PD models 52 , 70 . A recent study showed improvement in anxiety and depressive symptoms in a PD rat model with dizocilpine treatment, which was speculated to have occurred via Wnt signaling 54 . In summary, the use of NMDA antagonists is becoming more common in treating psychiatric symptoms, especially depression.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA activate NMDAR on hippocampal neurons, change synaptic plasticity and release excitatory neurotransmitters that condition and inhibit MK-801 in a non-competitive role to improve cell vitality ( 28 , 29 ). A further study has revealed that MK-801 treatment [0.2 mg/kg, intraperitoneal (IP)] increases NSC proliferation in the hippocampus of a rat model with Parkinson's disease ( 30 ). MK-801 treatment results in enhanced hippocampal neurogenesis in the model.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Studies have shown that 6-hydroxydopamine (6-OHDA) induced dopamine depletion in the SN (SNpc) leads to decreased NSC proliferation in SVZ and SGZ in rodents. 15 17 In contrast, D2/D3 receptor stimulation did not show any effect on NSC proliferation and DAergic neuronal differentiation in murine and human brain–derived neural progenitor cells (NPCs). 18 Interestingly, a study showed that MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)–induced dopamine depletion in the midbrain transiently increased NSC proliferation and postmitotic neuronal differentiation in hippocampal DG in mice.…”
Section: Introductionmentioning
confidence: 99%